Actual Problems of Economics Teaching in Higher School - S. V. Stepanova (Высшее образование в России)
The article examines the current problems of teaching economic specialties in Russian universities. According to the author, modern higher economic education is not focused on training specialists with the knowledge and values necessary to solve the problems of ensuring the economic sovereignty of the country. The reasons for this are both inside and outside the education system. To identify these causes and areas of concentration of problems, the author analyzed the current admission rules approved by universities in accordance with the regulatory documents of the Ministry of Education and Science; approaches to the assessment of applicants; the content of educational programs, their relationship with professional standards; curricula in the areas of training 38.03.01 “Economics”. The study used publicly available information posted on the websites of universities-leaders of the Expert RA Rating Agency ranking for 2020 in economics and management. The analysis revealed areas where the problems of higher economic education have a high degree of concentration. These include: the lack of uniform requirements for the initial knowledge of applicants; heterogeneity of the quality of the student audience by the level of initial knowledge; the inability of professional standards to orient universities to the formation of popular educational programs; the predominance of mathematical disciplines in the curricula, while reducing the list and volume of disciplines that form the worldview; unjustified shift of emphasis towards financial disciplines, formation of calculation skills instead of obtaining fundamental economic knowledge. Awareness of these problems will make it possible to make changes to curricula purposefully, and university graduates will be quickly involved in solving problems related to ensuring the economic sovereignty of the country, along with representatives of technical specialties.